PENGARUH DANA PIHAK KETIGA, NON PERFORMING FINANCING, DAN RETURN ON ASSET TERHADAP PEMBIAYAAN MUDHARABAH PADA BANK UMUM SYARIAH PERIODE 2014-2017 - Yuyun Hanifatusa’idah; Nur Diana; Muhammad Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTThe purpose of this research to determine the influence of Third Party Funds, Non Performing Financing and Return On Asset towards Mudharabah of Sharia Commercial Banks for the period 2014-2017. The data used in this study is secondary data. The population used is Sharia Commercial Banks at Bank Indonesia for the period 2014-2017. The sampling technique was done by purposing sampling method. The sample of this research is 11 companies with 4 years observation. Data analysis was done by using multiple linier regression method. The result of this study indicate that (1) Third Party Funds has a significant positive effect on mudharabah, with a significance level of 0,031 < 0,05. (2) Non Performing Financing has a significant positive effect on mudharabah, with a significance level of 0,013 < 0,05. (3) Return On Asset has a significant positive effect on mudharabah, with a significance level of 0,011 < 0,05. Keywords: Third Party Funds, Non Performing Financing and Return On Asset and Mudharabah.